Revitalizing the cultural values of Pencak Silat Kumango through the digitalization of local arts and culture - Irfan, Dedy; Asmara, Delvi; Tasrif, Elfi; Erdisna, Erdisna; Syukhri, Syukhri; Putra, Rido; Edidas, Edidas; Hidayat, Nuzul (Community Empowerment, 2025)
The wave of modernization threatens the survival of local cultural heritage, including Kumango Pencak Silat in Nagari Kumango, Tanah Datar. This community service program aims to revitalize traditional martial arts values through a digital learning media strategy. The implementation followed a participatory approach, involving the local community in video documentation workshops, interactive e-module development, and culture-based social media management. Results indicated a significant improvement in participants' digital competence, with an average score increase of 35 points. This initiative successfully transformed traditional techniques and philosophies into digital formats accessible to the younger generation. The program's success demonstrates that the integration of digital technology and local wisdom effectively strengthens cultural resilience and serves as a replicable model for preserving intangible cultural heritage in other indigenous communities.